Implementation of Digital Population Identity Policy in Public Services of the Population and Civil Registration Service of Parepare City, South Sulawesi Province - Nurfadillah; Monalisa Ibrahim; Andi Uceng (Global Writing Academica Researching and Publishing, 2026)
This study aims to analyze the implementation of Digital Population Identity (IKD) in public services at the Population and Civil Registration Office of Parepare City and identify factors that still pose obstacles to its implementation. This study used a descriptive qualitative method with George C. Edward III's implementation theory, which includes communication, resources, disposition, and bureaucratic structure, as well as Servqual theory in analyzing public services.The results indicate that the implementation of IKD has been quite successful, but there are still aspects that are not optimal. NVivo coding results indicate that resources obtained a percentage of 2.7%, reflecting the continued limitations in facilities, supporting devices, internet networks, and smartphones. In terms of public services, network errors were the most dominant obstacle, accounting for 5.9% of the time, while reliability was only 0.1%, indicating that service consistency is still affected by network disruptions and application technical issues. Furthermore, low levels of digital literacy also contribute to difficulties for some individuals using the Digital Population Identity (IKD). Therefore, improvements to facilities and infrastructure, strengthening of the network and application system, and increased outreach and support for the public are needed to optimize IKD implementation and support improvements in the quality of public services.